DIGITAL COMPETENCE OF TEACHERS IN THE USE OF ICT - Ibodullayeva Zubayda Sherzodovna (Science, education, innovation: modern tasks and prospects, 2025)
This article examines the digital competence of teachers in effectively utilizing Information and Communication Technologies (ICT) in the educational process. It highlights the essential digital skills required for planning, delivering, and evaluating lessons in technology-rich environments. The paper also addresses professional development needs, challenges in technology adoption, and the role of institutional support in enhancing teachers' digital literacy. Emphasis is placed on how digital competence contributes to improved student engagement and learning outcomes.